Robots Operating in Hazardous Environments 2017
DOI: 10.5772/intechopen.69375
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment Strategy for Collaborative Robot Installations

Abstract: Industrial resource efficiency can be improved if the safety barrier between humans and robots is removed, as this enables operators and robots to work side by side or in direct collaboration to solve a task, usually referred to as a collaborative robot installation. Even though technology development makes the barrier removal ever more feasible from a safety perspective, this still produces a possible hazardous working environment, and safety assessment strategies are crucial. A wide area of knowledge is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Other authors have identified similar characteristics, albeit from a slightly different perspective. For example, amongst the conditions for dealing with safety issues, Grahn et al identified the need to take all factors affecting safety into account, the need to ensure sufficient user acceptance, and the need to be sufficiently cost-effective to make cobots commercially interesting [17].…”
Section: Cobot Safety Is Dynamic and Not Limited To The Consideration...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have identified similar characteristics, albeit from a slightly different perspective. For example, amongst the conditions for dealing with safety issues, Grahn et al identified the need to take all factors affecting safety into account, the need to ensure sufficient user acceptance, and the need to be sufficiently cost-effective to make cobots commercially interesting [17].…”
Section: Cobot Safety Is Dynamic and Not Limited To The Consideration...mentioning
confidence: 99%
“…Knowledge deficits were considered the most significant barrier by [14], and were further broken down into (i) cobots and the technology in general, (ii) potential applications and ways of using cobots, (iii) reference cases, (iv) understanding of safety in general, (v) understanding and lack of safety legislation and unclarity of safety standards and metrics, (vi) risk (re-) assessment, and (vii) ease of deployment. The slower-than-expected uptake of collaborative systems is also attributed to the lack of confidence and knowledge with respect to ensuring safety [15,16] and is related to perceived unsafe feelings of operators towards cobots [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a trend towards parameters that are related to environmental indicators, such as energy consumption and emissions [13,14]. In a HRC setting it is also important to evaluate the most cost-efficient way to organize the layout where the operator and the robots can work safely together [15]. When analyzing utilization of digital tools for production preparation we define an 'efficient' utilization as utilization that increases created Value (V), or decreases the consumption of Resources (R) that are required for the Value creation, over time, i.e.…”
Section: Value and Resource Parameters For A Hrc Settingmentioning
confidence: 99%
“…However, the challenge is to understand the level of reliability for each software when utilizing these as a support for analysing hazards related to a HRC layout. This is important to manage since the risks needs to be re-evaluated if the application is changed [15].…”
Section: Aspects Related To Software Support For the Hrc Layout Designmentioning
confidence: 99%
“…Environmental indicators are also ever more important, such as emissions and energy consumption (Paju et al, 2010;Matta et al, 2019). In an HRC layout, evaluation of the most cost-efficient layout design, where the operator and the robots can work safely together, is also important (Grahn et al, 2017). Furthermore, 'Efficient' utilization of digital tools when designing HRC layouts is defined as utilization that increases or maintains created Value, and/or decreases Resource consumption required for the Value creation, over time, i.e.…”
Section: Value and Resource Parameters When Designing Hrc Layoutsmentioning
confidence: 99%